Research on damage visualization of concrete structures based on electrical resistance tomography - Su, Chenhui; Zhang, Wenchao; Zhao, Jianyu; Yang, Hongjuan; Li, Chengdong (Frontiers in Physics, 2022)
Concrete is used in the construction of high-rise buildings, large bridges, viaducts and other structures for a wide range of applications, and damage to the internal structure of concrete may to lead to catastrophic accidents. In this paper, electrical resistance tomography is applied to concrete structural damage detection. The electrical resistance tomography imaging reconstruction algorithm is studied. The advantages and disadvantages of five image reconstruction algorithms are investigated through simulation experiments as well as experiments, and the improved normalized image reconstruction algorithm is selected. The feasibility of the used electrical resistance tomography system is explored by conducting imaging experiments with water bodies, and the results show that the built system is feasible. Finally, using the resistive chromatography imaging system, a current excitation is applied to the concrete, and the data acquisition system collects the boundary voltage values carrying the internal conductivity distribution of the concrete, and images its internal structure through the image reconstruction algorithm. It is achieved to detect damage inside the concrete and to visualize the imaging when there are pores in the concrete structure and when water penetrates in the concrete structure.